Histopathological biomarkers and genotoxicity in gill and liver tissues of Nile tilapia Oreochromis niloticus from a polluted part of the Nile River, Egypt. Issue 2 (27th May 2016) - Baiomy, AA
Abstract : Fish health is affected by water pollution. Oreochromis niloticus collected during summer 2014 from El-Serw, a polluted site on the Nile River, were compared with fish from a reference site, El-Zamalek. Histopathological changes were detected in gill and liver tissue samples using light and electron microscopy. In addition, the degree of DNA damage was measured using the comet assay. To indicate the severity of water pollution at the two sites, physico-chemical properties and heavy metal concentrations were investigated. Gill damage, including lamellar cell hyperplasia and aneurysm, was observed in the fish samples from the polluted site. The livers of fish from the polluted area showed necrosis and an increase in melanomacrophage centres. Histochemical results confirmed a marked rise of gill mucopolysaccharides and a reduction of carbohydrate stored in hepatocytes. Electron microscopy revealed clear alterations in gill and liver tissue of fish from the polluted site. The comet assay showed highly significant DNA damage in tilapia collected from the polluted site, compared to those from the reference site. Histopathological biomarkers and the comet assay may therefore be sensitive indicators of exposure to mixtures of aquatic pollutants in Nile tilapia.